2002
DOI: 10.1038/sj.jhh.1001310
|View full text |Cite
|
Sign up to set email alerts
|

Systolic vs diastolic blood pressure: community burden and impact on blood pressure staging

Abstract: Systolic blood pressure (SBP) is a more frequent cardiovascular risk factor than diastolic blood pressure (DBP), and has a greater impact on blood pressure staging, though this can vary with age, sex and country. Therefore this paper compares SBP and DBP in terms of community burden and impact on blood pressure staging, among Spain's middle-aged population. Data were drawn from a cross-sectional study on a representative sample of the Spanish population aged 35-64 years. Blood pressure was determined under sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 7 publications
(8 reference statements)
2
18
1
Order By: Relevance
“…Other studies reported higher prevalence rates of hypertension among older adult population surveys in Tanzania in 2010 (69.9%, mean age 76 years), Tunisia in 2003 (69.3%, mean age 69 years) and Senegal in 2009 (65.4%, mean age 69.5 years) 22-24. Similar to Banegas et al25 and Onwubere et al,26 a larger percentage of participants in our study had ISH compared to IDH. ISH was also more common in those above 60 years of age, compared to IDH.…”
Section: Resultssupporting
confidence: 85%
“…Other studies reported higher prevalence rates of hypertension among older adult population surveys in Tanzania in 2010 (69.9%, mean age 76 years), Tunisia in 2003 (69.3%, mean age 69 years) and Senegal in 2009 (65.4%, mean age 69.5 years) 22-24. Similar to Banegas et al25 and Onwubere et al,26 a larger percentage of participants in our study had ISH compared to IDH. ISH was also more common in those above 60 years of age, compared to IDH.…”
Section: Resultssupporting
confidence: 85%
“…Similar to the study by Banegas et al [28], SBP constituted a greater community burden than DBP in this study. SBP was also more common in those >50 years of age when compared to DBP and greater proportion of subjects were upstaged in this study by SBP than DBP.…”
Section: Discussionsupporting
confidence: 91%
“…4 For example, Lloyd-Jones et al, 3 when evaluating blood pressure staging in 4962 patients, Framingham Heart Study subjects found that 94% had an elevated SBP but only 33% had elevated DBP. The older age of the Framingham subjects may explain why the percentages differ from the study Banegas et al 6 where the prevalence of systolic hypertension was 34.1% and diastolic hypertension, 30.9%.…”
Section: Evolution Of Importance Of Sbpcontrasting
confidence: 66%
“…In the survey by Banegas et al, 6 60.8% of untreated subjects had parallel staging of SBP and DBP, whilst 22.5% were upstaged on the basis of their SBP, and 16.7% on the basis of DBP: thus, if SBP criteria were applied, 83.3% would be correctly staged according to JNC-VI, compared with 77.5% using DBP criteria. Furthermore, SBP control was worse than DBP control, and SBP represents a greater impact on blood pressure staging as well as a substantial community burden than does DBP.…”
Section: Is Pulse Pressure a Better Predictor Of Risk?mentioning
confidence: 96%